The Effect of Scientific Events in Shopping Mall On Children’s Learning and Social Interaction: Case of Life Cycle of Butterfly & Formation of Rainbow - Türkmen, Hakan (International Journal Pedagogy of Social Studies, 2022)
This study, it is aimed to determine the effect of scientific events in shopping malls on children's interactions and learning. Thirty-three children selected by purposive sampling method were carried out by participating in scientific events in a shopping mall, one of the informal learning environments of a big city. Data were collected through interviews before the scientific event session, observations and drawings during the scientific event session, and open-ended questions after the scientific event session. Content and frequency analysis were used in the analysis of the data. Before the events, the children participating in the study had deficiencies and misconceptions in scientific knowledge, but a significant increase was observed in their scientific knowledge at the end of the event. In the science event children learned by doing and experiencing (hands-on) and they had no difficulty in expressing their knowledge. In addition, it was observed that those who do not know each other got along very quickly with other children during the event. Helping and sharing with their friends who have difficulties in handicraft skills is the clue that they contribute to the development of their social skills. It also showed that children not only learn from a teacher but also learn from their peers. Expressing that they have fun and enjoy the science events can be shown as proof that children have a good time. After the scientific events, they emphasized that the children want to participate in such events again because this environment including different activities was found so colorful and not boring by children. If families bring their children to these types of scientific events in the shopping mall, that will contribute to children’s school academic achievement and help them socialize. Based on the results of the study, it is suggested that the number of such science events should increase in shopping malls and the permanence of children's learning can also be searched.